Effect of perceived HIV risk on initiation of antiretroviral therapy during the universal test and treat era in South Africa - Sabina M. Govere; Sean Galagan; Boikhutso Tlou; Tivani Mashamba-Thompson; Ingrid V. Bassett; Paul K. Drain (BMC Infectious Diseases, 2021)
Abstract Background South Africa has not achieved the 90–90–90 goals, in part due to low rates of antiretroviral therapy (ART) initiation among those aware of their HIV status. Perceived risk of HIV at the time of testing may affect likelihood of rapid ART initiation. The purpose of this study was to evaluate factors associated with perceived risk of HIV and the relationship between perceived HIV risk and rapid ART initiation during the universal test and treat era which was adapted in October 2016. Methods We conducted a prospective study of adults undergoing HIV testing from October 2016–February 2019 at Ithembalabantu Clinic in Durban. Eligible participants reported not previously being diagnosed with HIV. Before HIV testing, participants were asked to assess their perceived HIV risk on a four-level scale. We categorized “definitely not” and “probably not going to acquire HIV” as a low perceived risk, and “probably will” and “definitely will become HIV-infected” as a high perceived risk of HIV infection. Participants were followed for up to 14 months following HIV testing to assess ART initiation. Results Among 1519 people newly diagnosed with HIV, 55% were female and mean age was 33 years. Among those, 1382 (90.9%) had a high HIV risk perception and 137 (9.1%) reported low HIV risk perception. In the low risk group individuals were more likely to be female (58% vs 55%), unemployed (62% vs 59%), have a partner with unknown HIV status (61% vs 55%) compared to the high risk group. 83.2% of those with low HIV risk perception reported previously HIV testing compared 91.5% of those with high HIV risk perception. In the multivariate model, males were associated with a higher chances of initiating ART compared to females (adjusted hazard ratio (aHR): 1.187, CI 1.187 (1.060–1.329) and being unemployed (aHR 0.767 CI (0.650–0.905). Those with a low HIV risk perception were less likely to initiate ART 125 (91%) vs 1310 (95%) p = 0.022), and took longer to initiate on ART after HIV diagnosis (11 days’ vs 4 days, p = 0.042). Conclusion Factors associated with high HIV risk perception included being unemployed, single, and having a partner of unknown HIV status. People living with HIV (PLHIV) in South Africa who had a low self-perceived risk to HIV infection were less likely to initiate ART. Assessing self-perceived risk of HIV infection may help direct counselling and improve ART initiation to achieve universal 90–90–90 goal.